Which Urban Plan for an Urban Heritage. An Overview of Recent Portuguese Practice on Integrated Conservation - Gonçalves, Adelino (2008)
This paper presents an overview of how integrated conservation of urban scale heritage is managed in the urban rehabilitation practice in Portugal and its relation with local urban planning. The central argument is that the safeguard of urban scale heritage is mainly a question of urban management and urban planning, which necessarily implies a framework that results from conciliation among the culture and the land use administrations. For that purpose, we consider that special attention to a cultural debate concerning the urban heritage concept itself plays a key role, once it can lead to a focus on urban rehabilitation practice, commonly spread and diffuse in its objectives. We also believe that integrated conservation practice doesn’t belong exclusively to one of the several land use plans of our top-down planning framework and therefore requires a crossmanagement strategy – top-down and bottom-up – and urban management skills to take advantage of each of those land use plans.